Focusing on Hofmeister series: Composition, structure and functional properties of pea protein extracted with food-related anions. (December 2022) - Liu, Yexue; Li, Xueying; Liu, Jiameng; Wei, Likun; Liu, Yihan; Lu, Fuping; Wang, Wenhang; Li, Qinggang; Li, Yu
Abstract: Hofmeister series effects have important impacts on hydration and stability of proteins during dissolution. However, Hofmeister anions in plant protein extraction are not yet clear. Here, the effects on pea protein extraction of some common food-compatible anions (CO3 2−, Citrate 3−, SO4 2−, C3 H5 O3 − (lactate), CH3 COO −, and Cl − ) in their Na-form were investigated. Native gel electrophoresis of dialyzed proteins revealed that CO3 2−, Citrate 3−, and SO4 2− decreased the intensity of 11S legumin fraction compared to C3 H5 O3 −, CH3 COO −, and Cl − . Also, pea protein extracted by the first three anions showed a higher denaturation state and exposed more hydrophobic regions to the aqueous solvent, as shown by the circular dichroism and fluorescence probe measurements, respectively. Accordingly, the techno-functional properties of the obtained proteins varied, depending on the Hofmeister order of each anion. A notable exception was represented by the proteins extracted by carbonate (a salting-out salt), whose small particle size and high solubility at pH 7 were more akin to that of the proteins extracted by salting-in salts. An effect which may be due to the synergistic effect of bicarbonate (the main ionic species present at pH 8) and chloride (necessary to bring, as HCl, carbonate solution to pH 8). In summary, Hofmeister anions are suitable for plant protein extraction, providing a promising approach to confer tunable properties to pea proteins and this may enhance the usability and application fields of pea protein. Graphical abstract: Image 1 Highlights: Structure and functional properties of pea protein are impacted by Hofmeister effect. Na2 CO3 solution resulted in a highest extraction yield of pea protein. NaCl extraction promotes the protein secondary structure folding. Na2 CO3 solution had a more impact on protein conformation than others salt. NaCl extracted pea protein had highest gelling temperature.